Retrospective miscue analysis and grade II pupils' comprehension skills - Lazaro, Lualhati B. (2007)
The study described and explored the reading behaviors of twenty second graders through RMA. It sought to identify the causes of miscues of grade two students and the effect of RMA on their comprehension skills. The sample was composed of 12 females and 8 males who scored the highest in the Metropolitan Reading Skills Achievement Test. Five RMA sessions were conducted to the students where miscues of a new story were discussed in each session. Students generated low level miscues because they relied on letter-sound relationships to determine meaning, and high level miscues because they relied on syntactic and semantic cues. RMA helped improve the comprehension skills of students as shown by the difference in their scores in the pretest and posttest. The instructional reading levels of 12 students increased by one up to three levels higher.
Thesis (M.A. Teaching the Early Grades (K-2))--University of the Philippines, Diliman.
Keywords: Reading (Elementary) -- Philippines -- Quezon City; Reading comprehension -- Philippines -- Quezon City; Miscue analysis; Reading comprehension -- Ability testing -- Philippines -- Quezon City